De novo and rare mutations in the HSPA1L heat shock gene associated with inflammatory bowel disease. Issue 1 (December 2017) - Takahashi, Shinichi; Andreoletti, Gaia; Chen, Rui; Munehira, Yoichi; Batra, Akshay; Afzal, Nadeem; Beattie, R.; Bernstein, Jonathan; Ennis, Sarah; Snyder, Michael
Abstract Background Inflammatory bowel disease (IBD) is a chronic, relapsing inflammatory disease of the gastrointestinal tract which includes ulcerative colitis and Crohn's disease. Genetic risk factors for IBD are not well understood. Methods We performed a family-based whole exome sequencing (WES) analysis on a core family (Family A) to identify potential causal mutations and then analyzed exome data from a Caucasian pediatric cohort (136 patients and 106 controls) to validate the presence of mutations in the candidate gene, heat shock 70 kDa protein 1-like (HSPA1L ). Biochemical assays of the de novo and rare (minor allele frequency, MAF < 0.01) mutation variant proteins further validated the predicted deleterious effects of the identified alleles. Results In the proband of Family A, we found a heterozygous de novo mutation (c.830C > T; p.Ser277Leu) inHSPA1L . Through analysis of WES data of 136 patients, we identified five additional rareHSPA1L mutations (p.Gly77Ser, p.Leu172del, p.Thr267Ile, p.Ala268Thr, p.Glu558Asp) in six patients. In contrast, rareHSPA1L mutations were not observed in controls, and were significantly enriched in patients (P  = 0.02). Interestingly, we did not find non-synonymous rare mutations in the HSP70 isoformsHSPA1A andHSPA1B . Biochemical assays revealed that all six rareHSPA1L variant proteins showed decreased chaperone activity in vitro. Moreover, three variants demonstrated dominant negative effects on HSPA1L and HSPA1A protein activity. Conclusions Our results indicate that de novo and rare mutations inHSPA1L are associated with IBD and provide insights into the pathogenesis of IBD, and also expand our understanding of the roles of HSP70s in human disease.